Toxoplasma gondii serine-protease inhibitor-1: a new adjuvant candidate for asthma therapy - Soto, Ariadna Soledad (2017)
Serine-proteases are important players in the pathogenesis of asthma, promoting inflammation and tissue remodeling. It’s also known that many serine protease inhibitors display immunomodulatory properties. TgPI-1 is a Toxoplasma gondii protein that exhibits broad spectrum inhibitory activity against serine proteases. In view of the increased prevalence of atopic disorders and the need to develop new treatment strategies we sought to investigate the potential of TgPI-1 for treating respiratory allergies. For this purpose, we developed a therapeutic experimental model. BALB/c mice were rendered allergic by intraperitoneal ovalbumin-alum sensitization and airway-challenged. Once the asthmatic phenotype was achieved, mice were intranasally treated with rTgPI-1 alone or with a mixture of rTgPI-1 and ovalbumin (OVA). A week later mice were given a secondary aerosol challenge. Treatment with rTgPI-1 alone or co-administered with OVA diminished bronchoalveolar eosinophilia, mucus production and peribronchial lung infiltration. This effect was accompanied by a lung resistance reduction of 26.3% and 50.3% respectively. Both treatments resulted in the production of lower levels of IL-4, IL-5, IFN-γ and regulatory IL-10 by thoracic lymph node cells stimulated with OVA. Interestingly, significant decreases in OVA specific IgE and T cell proliferation, and increases in FoxP3+ T cells at local and systemic levels were only detected when the inhibitor was administered along with OVA. These results show that both rTgPI-1 treatments reduced asthma hallmarks. However, co-administration of the inhibitor with the allergen was more effective. Hence, rTgPI-1 emerges as a novel adjuvant candidate for asthma treatment.